Discourse on the world university rankings: the lesson of english for university - V. Р. Shestak; N. V. Shestak (Высшее образование в России)
The paper examines the basic tendencies in the world science and the objectively necessary and sufficient conditions of English-language activity of Russian universities for increasingtheir competitive ability among the world class universities. The connection between constant losses of Russian universities in the international competition among universities and the level of their proficiency in English is analyzed. The connection of the prevailing criteria of estimation the quality of scientific results with the level of English language proficiency is shown. There are touched upon some recommendation regarding the solution of the problems.